2019
DOI: 10.1371/journal.pone.0220103
|View full text |Cite
|
Sign up to set email alerts
|

Self-care strategies and sources of knowledge on menstruation in 12,526 young women with dysmenorrhea: A systematic review and meta-analysis

Abstract: Introduction: Dysmenorrhea (period pain) is common and affects around three quarters of all young women under the age of 25. The majority of young women, for a variety of reasons, think of period pain as ‘normal’ and something to be managed or endured. This normalisation of pain often is reinforced by family and friends and results in young women using self-care strategies to manage their pain rather than seeking medical advice. This systematic review and meta-analysis examined observational studies reporting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
98
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(127 citation statements)
references
References 57 publications
6
98
1
5
Order By: Relevance
“…Nonetheless, a reduced prevalence of dysmenorrhea and absenteeism was identified during menstruation in women who did take contraceptives, which is in line with the previous literature, however, this treatment is known to have possible adverse effects and is not accepted by all women [31,32].A number of authors consider the need to study the strategies used for treating menstrual pain and symptoms [5,22]. Although the management of menstruation is influneced by a diversity of contextual factors such as social, cultural, and economical factors, Armour et al highlight the urgent need on a global level to provide greater information on self-care regarding the management of menstruation, as, currently, most women worldwide fail to choose the best self-care option in this matter [31]. In addition, the high rates of absenteeism identified due to menstrual pain and symptoms in our study may also be explained by the policies in place at the nursing faculty, which allow the students to make up for missed days during clinical placements, when students are unable to attend due to health issues.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Nonetheless, a reduced prevalence of dysmenorrhea and absenteeism was identified during menstruation in women who did take contraceptives, which is in line with the previous literature, however, this treatment is known to have possible adverse effects and is not accepted by all women [31,32].A number of authors consider the need to study the strategies used for treating menstrual pain and symptoms [5,22]. Although the management of menstruation is influneced by a diversity of contextual factors such as social, cultural, and economical factors, Armour et al highlight the urgent need on a global level to provide greater information on self-care regarding the management of menstruation, as, currently, most women worldwide fail to choose the best self-care option in this matter [31]. In addition, the high rates of absenteeism identified due to menstrual pain and symptoms in our study may also be explained by the policies in place at the nursing faculty, which allow the students to make up for missed days during clinical placements, when students are unable to attend due to health issues.…”
Section: Discussionsupporting
confidence: 88%
“…Several authors have found that many young women with dysmenorrhea are able to endure menstrual pain and symptoms, understanding these as a typical aspect of a woman's life, normalizing their own menstrual experiences, even if these entail limitations [27][28][29]. Ibuprofen or other over-the-counter nonsteroidal anti-inflammatory drugs are the current standard of care for dysmenorrhea, although when not taken to "stay ahead of the pain" they have less than 50% effectiveness [30,31]. Oladsu et al highlight the possible resistance to drugs in cases of dysmenorrhea, which is estimated at approximately 18%.…”
Section: Discussionmentioning
confidence: 99%
“…However, this also demonstrates that seeking professional help is not enough. In the last decade, several authors have noted the need to further study both the pharmacological and non-pharmacological management of menstrual pain [ 10 , 11 , 35 ], especially considering that 18% of non-steroidal anti-inflammatory treatments are ineffective for dysmenorrhea, the primary treatment for this condition [ 36 ]. There is increasing evidence of the efficacy of non-pharmacological methods for dysmenorrhea, such as aerobic exercise, yoga, taping and transcutaneous electrical nerve stimulation [ 20 , 21 , 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have shown that dysmenorrhea can significantly reduce quality of life and limit daily activities, especially in women with severe pain [ 8 , 9 ]. However, the majority of studies show that women suffering from dysmenorrhea generally do not seek professional medical help and recur to self-medication using non-steroidal anti-inflammatories [ 10 ]. This pain relief strategy is often ineffective and may have adverse side effects [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on this prostaglandin pathology, the most frequent treatment drugs for PD are nonsteroidal anti-inflammatory drugs (NSAIDs) as prostaglandin synthetase inhibitors. [ 7 , 8 ] When not responding to prostaglandin inhibitors, synthetic hormonal contraceptives may be administered to reduce prostaglandin synthesis and suppress dysmenorrhea. [ 4 ] However, such conventional treatments have disadvantages in terms of safety.…”
Section: Introductionmentioning
confidence: 99%